The Impact of British Imperialism on Education in Ghana - DJOUDI ,Elhachemi; BENCHAOUI, Abderrahmane; SELT, Djihad Affaf SELT (Faculty of Letters and Foreign Languages Department of English, 2017)
This dissertation’s objective is to examine the positive legacy left by British colonial rule on Ghana’s educational system. Ghana is a vivid example of a successful educational system in Africa, due to the impact of colonialism where the British had the main influence. The three components that contributed to result in the actual education system are the indigenous education, Islamic education and Western Christian education. The most recent and influential one in the education history of Ghana is the British colonial education. The Ghanaians with their national spirit called for independence but kept following the coloniser’s footsteps in matters which brought benefits to the nation. They gave a high priority to the education sector by declaring reforms and acts which were not radical but continuous to what the British had left. These acts improved the education and resulted in the development of other sectors as well. Such a model would be beneficial to some nations to help them develop, especially in the African scene.